A New Absorbable Synthetic Substitute With Biomimetic Design for Dural Tissue Repair. Issue 4 (2nd November 2015) - Shi, Zhidong; Xu, Tao; Yuan, Yuyu; Deng, Kunxue; Liu, Man; Ke, Yiquan; Luo, Chengyi; Yuan, Tun; Ayyad, Ali
Abstract: Dural repair products are evolving from animal tissue–derived materials to synthetic materials as well as from inert to absorbable features; most of them lack functional and structural characteristics compared with the natural dura mater. In the present study, we evaluated the properties and tissue repair performance of a new dural repair product with biomimetic design. The biomimetic patch exhibits unique three‐dimensional nonwoven microfiber structure with good mechanical strength and biocompatibility. The animal study showed that the biomimetic patch and commercially synthetic material group presented new subdural regeneration at 90 days, with low level inflammatory response and minimal to no adhesion formation detected at each stage. In the biological material group, no new subdural regeneration was observed and severe adhesion between the implant and the cortex occurred at each stage. In clinical case study, there was no cerebrospinal fluid leakage, and all the postoperation observations were normal. The biomimetic structure and proper rate of degradation of the new absorbable dura substitute can guide the meaningful reconstruction of the dura mater, which may provide a novel approach for dural defect repair.